Guardiões de sementes crioulas de feijão como agentes da conservação da agrobiodiversidade: um estudo de caso no sudoeste do Paraná - Telles, Carolini dos Santos (2019)
The emergence of agriculture triggered the occurrence of a social and cultural revolution on humanity. This, which has evolved over the centuries, has undergone successive transformations that have affected human societies in different times and places. However, the socio-environmental impacts triggered by revolutions, such as the Green Revolution, have become increasingly evident, such as the sharp reduction in the diversity of species and varieties of cultivated plants. The conservation of this agrobiodiversity, however, does not only imply an environmental issue but a food and nutritional security of the population, sustainable rural development, social inclusion and the fight against hunger and misery are directly or indirectly related to the conservation and use of agrobiodiversity resources. In this context, conserving such wealth is imperative and one of the ways to ensure such biodiversity is the "guardians of creole seeds" that keeps seeds / seedlings over time on their properties. Among the species of plants of importance for food, we have the common bean that is present in the diet of most brazilians and that due to its importance for food security and human nutrition is among the main cultures of the country. Under this situation, the objective of the work was to identify the context that the guardians of bean seeds of Creole are inserted, as well as the main challenges faced by these as maintainers of these cultivars. After an interview with the seed guardians it was possible to infer that these are present in well diversified contexts. However the reality in the process of maintaining seeds is very similar, as well as the main difficulties and desires of these. As a conclusion we emphasize the need for greater awareness of the population about the theme and support by government and universities to these guardians, as well as greater investments in research, technical assistance, courses among others. In addition, the possibility of income generation through maintenance of these seeds would be a good option in trying to strengthen the activity, however this is a little known and exploited by the farmers under study.